DETECTION OF CASH FLOW FROM OPERATION MANAGEMENT USING CLASSIFICATION AND TIMING - Debbianita, Debbianita; Hidayat, Vinny Stephanie; Mangunsong, Soddin; Destiana, Raden Shafira (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2020)
This study aims to examine whether management is proven to have cash flow from operation management (CFO management) using classification and timing in companies listed on the Indonesia Stock Exchange in 2017. The research method used is explanatory research, and the method of determining the sample used is the judgment sampling method. Testing the research hypothesis using the multiple regression analysis using eviews versin 6.0. The result from this study is no indication of CFO management using classification and timing.Â Key words: cash flow from operation management, classification, timingÂ